2021
DOI: 10.3390/bs11080109
|View full text |Cite
|
Sign up to set email alerts
|

Personal Values in Relation to Risk Intelligence: Evidence from a Multi-Mediation Model

Abstract: In a risk society, personal values can be important resources, useful for managing uncertainty and guiding people in the perception of risk. The goal of this article is to explore the relationship between risk intelligence and personal values. The participants were 731 Italian adults aged between 18 and 65 years (M = 30.25; DS = 10.71). The survey was composed of the following measures: Subjective Risk Intelligence Scale and Portrait Values Questionnaire. Data analyses have found significant relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…The study further reported the positive relationship of universalism with pro-environmental attitudes and behaviors, implying the influence of SET on one’s attitudes, intentions, and behaviors. Prior studies measured and studied SET and confirmed the importance of SET and the likelihood of individuals achieving various goals, as well as the intensity of motivation to work toward these goals ( Zammitti et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 82%
“…The study further reported the positive relationship of universalism with pro-environmental attitudes and behaviors, implying the influence of SET on one’s attitudes, intentions, and behaviors. Prior studies measured and studied SET and confirmed the importance of SET and the likelihood of individuals achieving various goals, as well as the intensity of motivation to work toward these goals ( Zammitti et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 82%
“…Among college students, risk intelligence affects how satisfied they feel about the chosen degree program (choice satisfaction) and how satisfied they feel about the degree course in terms of the utility of the competencies developed the future work, the improvement in realizing job aspirations and the positive effect on the future career (utility satisfaction; [55]). Subjective risk intelligence is influenced by values [56]. About the relationship between risk intelligence and other positive outcomes for individuals, Craparo et al [54] suggested that future studies could explore the relationship between risk intelligence and positive outcomes for individuals, such as life satisfaction.…”
Section: Positive Psychology and Life Designmentioning
confidence: 99%
“…The recent literature on positive psychology applied to career development has found that the feeling of satisfaction with the educational context is related to positive psychological resources that, in turn, enhance the capacity to imagine positive future scenarios and a positive orientation toward the future. The very recent literature on career development has underlined that satisfaction with school and university is related in emerging adults to effective career planning by the activation of career management skills and other non-intellective competencies (Kumar, 2006; Lent et al, 2007; Shalley et al, 2004; Zammitti et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%